The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/per.2099
|View full text |Cite
|
Sign up to set email alerts
|

How do Personality and Social Structures Interact with Each other to Predict Important Life Outcomes? The Importance of Accounting for Personality Change

Abstract: Personality is important for a range of life outcomes. However, despite evidence that personality changes across time, there is a concerning tendency for researchers outside of personality psychology to treat measures of personality as if they are non‐changing when establishing whether personality predicts important life outcomes. This is problematic when personality changes in response to outcomes of interest and creates a methodological issue that may result in misleading conclusions. We illustrate this meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Age was included as a covariate because previous work has cited changes in personality and relationship satisfaction over time (Bleidorn et al, ; Kurdek, ; Lucas & Donnellan, ; Roberts & DelVecchio, ; Robins, Fraley, Roberts, & Trzesniewski, ; Wortman, Lucas, & Donnellan, ), and age has a wide range in the current sample. Education (which is measured on a 1–12 scale, with 1 reflecting no schooling and 12 reflecting doctorate‐level education), a proxy for socioeconomic status (Boyce, Wood, Delaney, & Ferguson, ; Kajonius & Carlander, ; Mosca & McCrory, ), and gender (Lippa, ) are also well‐known correlates of the BFM traits. Given the strong theoretical and empirical rationale, we chose to include these covariates.…”
Section: Methodsmentioning
confidence: 99%
“…Age was included as a covariate because previous work has cited changes in personality and relationship satisfaction over time (Bleidorn et al, ; Kurdek, ; Lucas & Donnellan, ; Roberts & DelVecchio, ; Robins, Fraley, Roberts, & Trzesniewski, ; Wortman, Lucas, & Donnellan, ), and age has a wide range in the current sample. Education (which is measured on a 1–12 scale, with 1 reflecting no schooling and 12 reflecting doctorate‐level education), a proxy for socioeconomic status (Boyce, Wood, Delaney, & Ferguson, ; Kajonius & Carlander, ; Mosca & McCrory, ), and gender (Lippa, ) are also well‐known correlates of the BFM traits. Given the strong theoretical and empirical rationale, we chose to include these covariates.…”
Section: Methodsmentioning
confidence: 99%
“…In a narrative review of the literature, Dolan, Peasgood, and White (2008) emphasized the importance of controlling for various individual difference correlates of well-being, such as health, in order to achieve an accurate estimate of the nature and size of personality–well-being associations. It is therefore surprising that empirical studies investigating the role of personality for well-being have either not taken into account physical and cognitive health (e.g., Boyce, Wood, Delaney, & Ferguson, 2017; Hahn, Johnson, & Spinath, 2013; Magee et al, 2013; Schimmack, Oishi, Furr, & Funder, 2004) or have exclusively used self-reported measures (e.g., Ha & Kim, 2013; Mroczek & Spiro, 2005). Although self-report measures are unique indicators of health, relying only on self-report in the context of personality–well-being associations may be problematic because these are partly rooted in individual difference characteristics such as personality.…”
Section: Trajectories Of Subjective Well-being In Old Agementioning
confidence: 99%
“…Future work should redress this and also seek to determine whether the buffering effect of cognitive ability extends to other clinical diagnoses known to vary with SES such as anxiety disorders (Stansfield et al ., 2011). Second, due to the concurrent timing of our moderator and outcome measures, we cannot infer that cognitive ability levels were not affected by the emergence of mental health problems which could result in inconsistent estimates (Boyce et al ., 2017). Whilst the issue of measurement timing cannot be directly addressed with the Understanding Society data, we note that this interpretation does not apply to previous reporting of this key interaction using longitudinal panel data in which cognitive ability was measured during childhood and many years prior to measurements of adult health (Bridger and Daly, 2017).…”
Section: Discussionmentioning
confidence: 99%